Iklim Organisasi dan Kepuasan Kerja Pegawai Bank Tabungan Negara - Afiah Mukhtar (Jurnal Manajemen Perbankan Keuangan Nitro, 2021)
The purpose of this study was to determine the effect of organizational climate on job satisfaction of the employees of the Bank Tabungan Negara (BTN) Panakkukang Makassar Branch. The number of respondents in this study were 40 employees using a simple linear regression analysis method and using primary data sources through interviews and questionnaires (Licker scale instruments). Based on the results of the study, it was found that organizational climate has a positive and significant influence on employee job satisfaction